2010
DOI: 10.1073/pnas.1011053108
|View full text |Cite
|
Sign up to set email alerts
|

Global declines in oceanic nitrification rates as a consequence of ocean acidification

Abstract: Ocean acidification produced by dissolution of anthropogenic carbon dioxide (CO 2 ) emissions in seawater has profound consequences for marine ecology and biogeochemistry. The oceans have absorbed one-third of CO 2 emissions over the past two centuries, altering ocean chemistry, reducing seawater pH, and affecting marine animals and phytoplankton in multiple ways. Microbially mediated ocean biogeochemical processes will be pivotal in determining how the earth system responds to global environmental change; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
260
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(295 citation statements)
references
References 48 publications
17
260
2
2
Order By: Relevance
“…Of significant concern is the potential impact of OA on the processes involved in the biogeochemical cycling of nitrogen (N) and, in particular, nitrification; a key microbial process through which remineralized N in the form of ammonia (NH 3 ) is oxidized to inorganic nitrite (NO 2 − ) and subsequently to nitrate (NO 3 − ). A number of recent and past studies have demonstrated an inhibitory effect of decreasing pH on water column nitrification activity [Beman et al, 2011;Huesemann et al, 2002;Jones, 1992;Stein et al, 1997]. The implications of such an effect on ecosystem function could be significant with modeling studies suggesting that substantial reductions in water column nitrification over the next century would affect nutrient stoichiometry, denitrification and by extension marine productivity and the biological carbon pump [Beman et al, 2011;Blackford and Gilbert, 2007].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of significant concern is the potential impact of OA on the processes involved in the biogeochemical cycling of nitrogen (N) and, in particular, nitrification; a key microbial process through which remineralized N in the form of ammonia (NH 3 ) is oxidized to inorganic nitrite (NO 2 − ) and subsequently to nitrate (NO 3 − ). A number of recent and past studies have demonstrated an inhibitory effect of decreasing pH on water column nitrification activity [Beman et al, 2011;Huesemann et al, 2002;Jones, 1992;Stein et al, 1997]. The implications of such an effect on ecosystem function could be significant with modeling studies suggesting that substantial reductions in water column nitrification over the next century would affect nutrient stoichiometry, denitrification and by extension marine productivity and the biological carbon pump [Beman et al, 2011;Blackford and Gilbert, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent and past studies have demonstrated an inhibitory effect of decreasing pH on water column nitrification activity [Beman et al, 2011;Huesemann et al, 2002;Jones, 1992;Stein et al, 1997]. The implications of such an effect on ecosystem function could be significant with modeling studies suggesting that substantial reductions in water column nitrification over the next century would affect nutrient stoichiometry, denitrification and by extension marine productivity and the biological carbon pump [Beman et al, 2011;Blackford and Gilbert, 2007]. However, the impact of OA on nitrification within sediments has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean acidification is also predicted to reduce microbial production of nitrate from ammonium (Beman et al, 2011), which could have major consequences for oceanic primary production because a significant fraction of the nitrate used by phytoplankton is generated by nitrification at the ocean surface (Yool et al, 2007). Major consequences of such changes over regional scales will probably include (1) reductions in primary production combined with (2) shifts from diatom-dominated (low SA:V ratio) phytoplankton assemblages with high POC-export efficiencies to picoplankton communities (high SA:V ratio) characterized by low export efficiencies Morán et al, 2010;Morán et al, 2015).…”
Section: The Abyssal Zonementioning
confidence: 99%
“…A second impact of anthropogenic CO 2 emissions is ocean acidification, which refers to the ongoing decline in ocean pH and the reduction in the ocean's carbonate mineral saturation state, with possible negative consequences for marine life [3][4][5]. Other geochemical and physical consequences of an increasingly acidic ocean include effects on metal speciation, reduced NH 3 /NH 4 + ratios (probably affecting ammonia oxidation rates), the marine source of atmospherically active trace gases and alteration of underwater sound absorption [6][7][8][9].…”
mentioning
confidence: 99%